Preoperative magnetic resonance cholangiopancreatography before planned laparoscopic cholecystectomy: is it necessary? - Rhaiem, Rami (J Res Med Sci, 2019)
BACKGROUND: The most feared complication of laparoscopic cholecystectomy (LC) is biliary tract injuries (BTI). We conducted a prospective study to evaluate the role of preoperative magnetic resonance cholangiopancreatography (MRCP) in describing the biliary tract anatomy and to investigate its potential benefit to prevent BTI. MATERIALS AND METHODS: From January 2012 to December 2016, 402 patients who underwent LC with preoperative MRCP were prospectively included. Routine intraoperative cholangiography was not performed. Patients' characteristics, preoperative diagnosis, biliary anatomy, conversion to laparotomy, and the incidence of BTI were analyzed. RESULTS: Preoperative MRCP was performed prospectively in 402 patients. LC was indicated for cholecystitis and pancreatitis, respectively, in 119 (29.6%) and 53 (13.2%) patients. One hundred and five (26%) patients had anatomical variations of biliary tract. Three BTI (0.75%) occurred with a major BTI (Strasberg E) and two bile leakage from the cystic stump (Strasberg A). For these 3 patients, biliary anatomy was modal on MRCP. No BTI occurred in patients presenting “dangerous” biliary anatomical variations. CONCLUSION: MRCP could be a valuable tool to study preoperatively the biliary anatomy and to recognize “dangerous” anatomical variations. Subsequent BTI might be avoided. Further randomized trials should be designed to assess its real value as a routine investigation before LC.